ChemInform Abstract: Straightforward Approach Toward Dihydrothiazoles via Intramolecular Bromocyclization. Issue 1 (17th December 2015) - Sadat‐Ebrahimi, Seyed Esmail; Ganjizadeh Zarj, Marzieh; Moghimi, Setareh; Yahya‐Meymandi, Azadeh; Mahdavi, Mohammad; Arab, Saman; Shafiee, Abbas; Foroumadi, Alireza
Abstract: The intramolecular bromium ion‐assisted cyclization of benzoyl chlorides furnishes dihydrothiazole derivatives by an easy procedure.